2016
DOI: 10.5546/aap.2016.eng.319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-perception of physical fitness and proposal for standards among Chilean adolescent students: the EAPAF study

Abstract: Introduction: Physical fitness may be assessed among children and adolescents in a quantitative and qualitative manner. At present, in Chile, there are no tools available to assess self-perception of physical fitness. Therefore, the purpose of this study was to develop a valid and reliable instrument that would allow to assess selfperception of physical fitness among adolescents and propose standards for age and sex. Material and methods: A survey was administered among adolescent students from six public scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The QAPA is a short questionnaire created specifically to facilitate the children’s understanding regarding self-perception of physical fitness in strength, flexibility, body weight, general fitness, and cardiorespiratory fitness. The questions were written originally in Portuguese based on another questionnaire [ 26 , 36 ]. The QAPA presents a consistency and reliability of 0.70–0.80 [ 18 ] and a significative ( β ’s = − 0.17 and 0.45; p =0.001) association with body mass index and cardiorespiratory fitness, suggesting that it is a valid instrument to measure SPPF [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QAPA is a short questionnaire created specifically to facilitate the children’s understanding regarding self-perception of physical fitness in strength, flexibility, body weight, general fitness, and cardiorespiratory fitness. The questions were written originally in Portuguese based on another questionnaire [ 26 , 36 ]. The QAPA presents a consistency and reliability of 0.70–0.80 [ 18 ] and a significative ( β ’s = − 0.17 and 0.45; p =0.001) association with body mass index and cardiorespiratory fitness, suggesting that it is a valid instrument to measure SPPF [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, traditional evaluations of children’s physical fitness have not been applied due to social distancing and lockdown. Thus, previous studies have shown that questionnaires are adequate resources for monitoring indicators related to fitness, physical activity, and health in children in social distancing context, mainly in lockdown [ 17 , 18 , 25 , 26 ]. Some cross-sectional diagnoses were made indicating that sedentary behavior, low levels of physical activity, and low levels of physical fitness were evident [ 14 , 17 , 18 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%